1994
DOI: 10.1164/ajrccm.150.6.7952634
|View full text |Cite
|
Sign up to set email alerts
|

Movement/arousals. Description, classification, and relationship to sleep apnea in children.

Abstract: Movement/arousal has been described as a characteristic of adult obstructive sleep apnea syndrome (OSAS), but opinions differ as to whether or not OSAS in children increases the frequency of movement/arousal. The problem that we decided to address was the lack of a comprehensive definition and characterization of movement/arousals in children. We therefore quantified and classified movement/arousals during nocturnal polysomnography in 15 children 5.2 +/- 2.7 SD yr of age being evaluated for OSAS. Movement/arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(121 citation statements)
references
References 17 publications
4
112
0
5
Order By: Relevance
“…4 Obstructive sleep apnea should be excluded in any polysomnographic assessment of JF, because it has also been shown to be associated with excessive motor activity during sleep in children. 14 Our polysomnographic data confirm the finding of decreased sleep efficiency reported by Roizenblatt et al 3 However, sleep efficiency could be reduced by several factors such as prolonged sleep latency, reduced total sleep time, and increased wakefulness periods during sleep. We found alterations in all of these domains in our study.…”
Section: Discussionsupporting
confidence: 91%
“…4 Obstructive sleep apnea should be excluded in any polysomnographic assessment of JF, because it has also been shown to be associated with excessive motor activity during sleep in children. 14 Our polysomnographic data confirm the finding of decreased sleep efficiency reported by Roizenblatt et al 3 However, sleep efficiency could be reduced by several factors such as prolonged sleep latency, reduced total sleep time, and increased wakefulness periods during sleep. We found alterations in all of these domains in our study.…”
Section: Discussionsupporting
confidence: 91%
“…However, Younes demonstrated that adults with OSAS may on occasion have an increase in flow during induced obstructions sufficient to sustain minute ventilation without arousal (10). In children with OSAS, obstructive events frequently end without a visible electrocortical arousal (11,12), and the sleep architecture remains intact (7). Mechanisms other than frank arousal therefore must also be operative in children, including reflex increases in pharyngeal dilator activity, as discussed above, and alterations in respiratory timing.…”
Section: Children With Osas Have An Increased Genioglossus Emgmentioning
confidence: 99%
“…Because criteria for arousals have not yet been developed for children, arousals were defined as recommended by the American Sleep Disorders Association Task Force report 45 using the 3-second rule and/or the presence of movement arousal. 46,47 Height and weight were obtained using standard techniques from each child. BMI then was calculated (body mass/height 2 ) and was expressed as relative BMI (relBMI), using the following formula: (BMI/BMI of the 50th percentile for age and gender) ϫ 100, based on standardized percentile curves.…”
mentioning
confidence: 99%